Theology at the limit? : an investigation of Richard Kearney’s philosophical hermeneutics in search of a responsible theological hermeneutic - Pretorius, Helgard Meyer (Stellenbosch : Stellenbosch University, 2015)
Thesis (MTh)--Stellenbosch University, 2015.